On The Trajectory of Boko Haram Terrorism in Nigeria: Socio-Economic Challenges and Intervention Strategies for Conflict Resolution - Olofinbiyi, Sogo Angel (Asian Journal of Interdisciplinary Research, 2019)
Approximately a decade of Boko Haram catastrophic enterprises in Nigeria has described the Islamist terrorist group as an anathema to sustainable development as well as the nation’s most protracted stand-off of recent times. The study employed a qualitative methodological approach of in-depth interviews to examine the multi-faceted challenges of the crisis in Nigeria. The study unfolds a great deal of deplorable effects associated with gradual underdevelopment of the Nigerian state, particularly in the areas of socio-economic, political, religious, educational, agricultural, and health advancement of the country. With Boko Haram’s persistent enterprise flourishing in Nigeria and no lasting solutions hitherto in sight, the study recommends peaceful negotiation as an immediate response to the crisis and pre-emptive legal measures as a remote solution to address such problem should it arise in the nearest future.